2021
DOI: 10.1111/medu.14539
|View full text |Cite
|
Sign up to set email alerts
|

Entrustable professional activities in entry‐level health professional education: A scoping review

Abstract: Entrustable professional activities (EPAs) are a recent enhancement to competency‐based health professional education that describe the observable work done by a competent health professional. Through defining education outcomes in a work‐based context, EPAs offer potential to identify skill gaps in individual or student cohorts and focus improvements. Entrustable professional activities have been pioneered and gained rapid acceptance in postgraduate medical education; however, less is known about their applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…This means that evidence, data collection, interaction with others, and indeed the integration of other theories or models may be used at any point in the action cycle. For instance, the frequently used Delphi consensus building approach 16 could be implemented for an action cycle phase. The outer action cycle begins at the base of the framework and rotates clockwise.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This means that evidence, data collection, interaction with others, and indeed the integration of other theories or models may be used at any point in the action cycle. For instance, the frequently used Delphi consensus building approach 16 could be implemented for an action cycle phase. The outer action cycle begins at the base of the framework and rotates clockwise.…”
Section: Methodsmentioning
confidence: 99%
“…The primary drivers to incorporate EPAs that validate practitioner competencies are patient safety, patient-centered care, 9,16,17 and the optimization of the student experience to meet industry standards. A recent scoping review (N = 30) revealed that EPAs are used in the United States, Europe, Australia, and Central America in pharmacy, physician assistant, and dietitian programs as well as medical education programs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…EPAs have enjoyed huge interest in all domains of health professions in many countries and constitute an important area of ongoing scholarly work. [1][2][3][4] In the literature, EPAs have been called objectives for education, a tool for assessment and sometimes even specific competencies. It is useful to reiterate here that each of these alone are not the best characterizations of EPAs.…”
Section: Principles Of Entrustable Professional Activities For Educat...mentioning
confidence: 99%